Pemanfaatan Tote Bag Sebagai Media Pembelajaran Seni Lukis di SMP Negeri 10 Semarang - Shofiyyah Prasetyani; Ratih Ayu Pratiwinindya (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This research was motivated by the dominance of conventional media in junior high school painting lessons, which results in less varied and contextual learning experiences for students. This study aimed to describe the use of Tote Bags as a learning medium in painting instruction at SMP Negeri 10 Semarang. The research employed a desctiptive qualitative approach with data collection techniques including observation, semi-structured interviews, questionnaires, and documentation during eight-grade painting lessons. The focus of the study covered the learning process in the stages of planning, implementation, and evaluation, as well as the analysis of students’ artworks and responses toward the use of Tote Bags. The use of Tote Bags in painting lessons not only served as a medium for studentss to express creativity, but also increased student engagement during the learning process. The learning activities were conducted using the Project Based Learning (PJBL) model and involved 32 eight-grade students. The results showed that use of Tote Bags as a learning medium was able to enhance student engagement, creativity, and motivation in creating artworks. Students’ artworks demonstrated visual diversity, both figurative and decorative, through more varied explorations of color, composition, and form compared to the use of paper media. In addition, students responded positively because Tote Bags have aesthetic, functional, and environmentally friendly values. Therefore, Tote Bags can be considered a contextual learning medium that supports meaningful and creative learning experiences in art education.